Immunoglobulin G subclass concentrations and infections in children and adolescents with severe asthma - Moraes Lui, Cleonir de; Oliveira, Lea Campos; Diogo, Constância Lima; Kirschfink, Michael; Grumach, Anete Sevciovic (Pediatric allergy and immunology, 2002)
It was the aim of this study to investigate possible dysfunctions of the humoral immune system in asthmatic children with frequent respiratory infections. Forty-one severe asthmatics (7-15 years of age), classified according to the Second Brazilian Consensus in Asthma (1998), were divided into two groups: group I (n = 12) had recurrent respiratory infections; and group II (n = 29) were without recurrent respiratory infections. Immunoglobulin (Ig)G, IgA and IgM levels (nephelometry), and IgE (radioimmunoassay) and IgG subclasses (enzyme-linked immunosorbent assay), were evaluated using standard methods. Asthmatics with recurrent infections presented with worse clinical evolution, an increased number of hospital admissions, and a higher need of medication than the children without recurrent infections. There were no significant differences between the mean values of IgG, IgA or IgM levels, or IgE or IgG subclasses, in patients of both groups. A complete IgA deficiency was detected in two patients of group I (one was associated with IgG subclass deficiency). Deficiency of one or more IgG subclasses was verified in eight of 12 (66%) children from group I and in 16/29 (55%) from group II. The following deficiencies were found in both groups: IgG3 (10/41), IgG4 (three of 41), IgG2 (two of 41), IgG1 (one of 41), IgG3-IgG4 (four of 41), IgG1-IgG3 (two of 41), and IgG1-IgG3-IgG4 (one of 41). There were a higher proportion of children with low IgG4 levels in group I than in group II (p = 0.01). To conclude, IgA and IgG subclass deficiencies were detected in both severely asthmatic groups, with a predominance of IgG3 subclass deficiency. However, low IgG subclass levels appear not to be a suitable predictor of the development of infections in asthmatic children.